A microRNA‐328 binding site in PAX6 is associated with centrotemporal spikes of rolandic epilepsy. Issue 7 (2nd June 2016) - Panjwani, Naim; Wilson, Michael D.; Addis, Laura; Crosbie, Jennifer; Wirrell, Elaine; Auvin, Stéphane; Caraballo, Roberto H.; Kinali, Maria; McCormick, David; Oren, Caroline; Taylor, Jacqueline; Trounce, John; et al.
Abstract: Objective: Rolandic epilepsy is a common genetic focal epilepsy of childhood characterized by centrotemporal sharp waves on electroencephalogram. In previous genome‐wide analysis, we had reported linkage of centrotemporal sharp waves to chromosome 11p13, and fine mapping with 44 SNPs identified the ELP4 ‐ PAX6 locus in two independent US and Canadian case–control samples. Here, we aimed to find a causative variant for centrotemporal sharp waves using a larger sample and higher resolution genotyping array. Methods: We fine‐mapped the ELP4 ‐ PAX6 locus in 186 individuals from rolandic epilepsy families and 1000 population controls of European origin using the Illumina HumanCoreExome‐12 v1.0 BeadChip. Controls were matched to cases on ethnicity using principal component analysis. We used generalized estimating equations to assess association, followed up with a bioinformatics survey and literature search to evaluate functional significance. Results: Homozygosity at the T allele of SNP rs662702 in the 3′ untranslated region of PAX6 conferred increased risk of CTS: Odds ratio = 12.29 (95% CI: 3.20–47.22), P = 2.6 × 10 −4 and is seen in 3.9% of cases but only 0.3% of controls. Interpretation: The minor T allele of SNP rs662702 disrupts regulation by microRNA‐328, which is known to result in increased PAX6 expression in vitro. This study provides, for the first time, evidence of a noncoding genomic variant contributing to the etiology of a common human epilepsy via a posttranscriptional regulatory mechanism.